The inverted class pedagogical model to improve the english language learning - Martínez-Salas, Melissa M. (2019)
The purpose of the research was to demonstrate how the application of the Inverted Class pedagogical model (Flipped Classroom) improves learning in English grammar proficiency in students of the Working Adult program, UPN, Lima-2018. The type of research was applied, scientific method and quasi-experimental method of explanatory level. The design was quasi-experimental with two equivalent groups and quantitative approach measurement. The sample consisted of 40 students of the program. The data collection technique was the evaluation for both groups a pretest and posttest test with their checklist instrument. A survey was applied to the students of the experimental group, observation sheet of learning sessions. The hypothesis was tested using the Student's T statistic for independent samples, using the SPSS version 24 program, with 5% margin of error, with P-value = 0 less than 0.05 significance. The arithmetic mean in the posttest for the control group was 62.5 and for the experimental group it reached 86.3, with a significant difference for both variables. Concluding on the improvement of learning in English grammar proficiency in the students of the program.